Cardiovascular risk and lifetime benefit from preventive treatment in type 2 diabetes: A post hoc analysis of the CAPTURE study. Issue 2 (24th October 2022) - Østergaard, Helena Bleken; Humphreys, Valerie; Hengeveld, Ellen Margo; Honoré, Julie Broe; Mach, François; Visseren, Frank L. J.; Westerink, Jan; Yadav, Gourav; Mosenzon, Ofri; ,
Abstract: Aim: To assess the potential gain in the number of life‐years free of a (recurrent) cardiovascular disease (CVD) event with optimal cardiovascular risk management (CVRM) and initiation of glucose‐lowering agents with proven cardiovascular benefit in people with type 2 diabetes (T2D). Materials and Methods: 9, 416 individuals with T2D from the CAPTURE study, a non‐interventional, cross‐sectional, multinational study, were included. The diabetes lifetime‐perspective prediction model was used for calculating individual 10‐year and lifetime CVD risk. The distribution of preventive medication use was assessed according to predicted CVD risk and stratified for history of CVD. For the estimation of absolute individual benefit from lifelong preventive treatment, including optimal CVRM and the addition of glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) and sodium‐glucose co‐transporter‐2 inhibitors (SGLT‐2is), the model was combined with treatment effects from current evidence. Results: GLP‐1 RA or SGLT‐2i use did not greatly differ between patients with and without CVD history, while use of blood pressure‐lowering medication, statins and aspirin was more frequent in patients with CVD. Mean (standard deviation [SD]) lifetime benefit from optimal CVRM was 3.9 (3.0) and 1.3 (1.9) years in patients with and without established CVD, respectively. Further addition of a GLP‐1 RA and an SGLT‐2i in patients with CVD gave an added mean (SD) lifetime benefit of 1.2 (0.6) years. Conclusions: Life‐years gained free of (recurrent) CVD by optimal CVRM and the addition of a GLP‐1 RA or aSGLT‐2i is dependent on baseline CVD status. These results aid individualizing prevention and promote shared decision‐making in patients with T2D.